Sex-Related Differences of Weight Bearing and Non-Weight Bearing Muscle Properties - Omid Nabavizadeh; Ashley A. Herda (Muscles, 2023)
This study evaluated muscle composition, quality, and strength of non-weight bearing and weight bearing muscles between males and females. Twenty-eight, healthy males (n = 14; mean ± SD; age = 25.1 ± 4.2 years; height = 181.9 ± 10.6 cm; weight = 91.6 ± 17.2 kg) and females (n = 14; age = 25.0 ± 3.4 years; height = 165.9 ± 6.9 cm; weight = 66.0 ± 10.2 kg) underwent body composition assessment to estimate body fat (%BF) and total-body, arm, and leg fat-free mass (TFFM, ArmFFM, and LegFFM, respectively) and muscle composition via B-mode ultrasound to measure muscle cross-sectional area (mCSA), echo intensity (EI), and thickness (mT) of four muscles [rectus femoris (RF), vastus lateralis (VL), flexor digitorum superficialis (FDS), and flexor carpi radialis (FCR)]. Additionally, upper- [handgrip strength (HG)] and lower-body [leg extension (LE)] maximal strength were measured, recorded, and expressed relative to FFM to determine muscle quality (MQ) for the dominant arm and leg, respectively. Males had greater TFFM, ArmFFM, and LegFFM (p < 0.001), mCSA for RF, VL, FCR, and FDS (p < 0.001), and mT for RF, VL (p < 0.001–0.006). Females had greater EI for RF, VL, and FDS (p = 0.003–0.01). Negative correlations were identified between EI and MQ for all muscles in males and females, however, no significance was determined. Despite the sex differences in absolute strength and size, muscle quality (relative strength) was not different for the upper nor lower body.